Efficiency of saturated vertical-flow filters planted with Panicum maximum reeds for passive wastewater treatment. Issue 5 (23rd February 2023) - Kpannieu, Dan Eude; Mallet, Martine; André, Erwan; Coulibaly, Lacina; Ruby, Christian
ABSTRACT: A vertical-flow unit containing four filters filled with shale was used to study the removal of phosphorous, nitrogen and organic matter of an urban residual wastewater during a period of 90 days. The influence of both the shale granulometry and the plant density of Panicum Maximum were studied. The decrease of the shale granulometry led to a significant improvement of all the measured parameters, while the presence of plants did only influence the phosphate retention with a lower extent. By comparing the results to previous studies, we hypothesised that the effect of the root system of Panicum maximum would be different depending on the size and the depth of the reactors. For practical application, adjusting the material granulometry was proposed to be the most important parameter for improving the filtration efficiency. Concomitantly, adjusting the plant density helps to control the clogging percentage of the filters. GRAPHICAL ABSTRACT: UF0001